The Salvational Process in Relationships: A View from Projective-Introjective Identification and Repetition Compulsion - Gostecnik, Christian (Journal of religion and health, 2009)
On the basis of mechanisms such as projective-introjective identification, basic affect, affect regulation, and repetition compulsion, we shall try to explain the essence of intrapsychic, interpersonal, and relational family dynamics. We will also try to explain how relational connections mutually intertwine in the family system, what sustains them, and why they are created and recreated again and again. It is in this regard that we will also be able to consider the essential salvational process, which occurs precisely on the basis of these mechanisms, that is, those that represent fundamental purification and salvation. Some basic biblical theological concepts are applied. These provide the basis for integrating the psychological and theological domains of family systems.